Subclinical hypothyroidism among patients with depressive disorders - Zahari Sham, Siti Yazmin; Umar, Nor Aini; Hambali, Zarida; Razali, Rosdinom; Abdul Manaf, Mohd Rizal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Subclinical hypothyroidism (SHT) is a biochemical diagnosis, defined as an elevated Thyroid Stimulating Hormone (TSH) with normal free thyroxine (FT4). It affects 4-10% of the adult population and is more prevalent in elderly women. Its commonest cause is autoimmune thyroiditis, detected by anti-thyroid peroxidase antibody (TPO-Ab). About 2-5% of SHT patients progress to overt hypothyroidism annually. The SHT prevalence among depressed patients ranges between 3% and 17%. This study aimed to determine the prevalence of SHT and TPO-Ab positivity among patients diagnosed with depressive disorders. It was a cross-sectional study carried out in the Universiti Kebangsaan Malaysia Medical Centre over a 12 months period. Serum TSH, FT4 and TPO-Ab were measured. Results showed that 82% of depressed patients were euthyroid, 4% had SHT, 11% had subclinical hyperthyroidism and 2% had discordant thyroid function. TPO-Ab positivity among the subjects was 7%, one of whom had SHT. In conclusion, the prevalence of SHT and TPO-Ab positivity in the study population, at 4% and 7%, respectively, were comparable to previous findings.